DeCovidation = Deinstitutionalization. Independent Living and Inclusion in the Community - Genienė, Rasa (Socialinė teorija, empirija, politika ir praktika, 2020)
The global coronovirus (Covid-19) pandemic has been revealed what about half of the world’s deaths are recorded in large institutions of the elderly and people with disabilities, and these are later thought to be incentives for states to take active deinstitutionalisation efforts. In order for deinstitutionalisation actions to respond to its ideological origins, which lie in the provisions of the United Nations Convention on the Rights of Persons with Disabilities, in the necessary legal instruments and in clarifying that Member States are responsible. The article reveals how the deinstitutionalisation processes that have already started are implemented and evaluated in Central and Eastern Europe and discusses their problems. Content analysis was used to investigate the Soviet regime, leading to the implementation of official and alternative (shadow) reports on the United Nations Convention on the Rights of Persons with Disabilities.
Keywords: deinstitutionalisation; independent living; inclusion in the community; group living home; corona virus